Sell more faster the ultimate sales playbook for startups - Schwartzfarb, Amos 1973- (John Wiley & Sons, Inc., 2019)
"From the experts at Techstars comes the elemental, essential, and effective strategy that will help any startup identify, build, and grow their customers from day 1. Most startups fail because they can't grow revenue early or quickly enough. Startup CEOs will tell you their early missteps can be attributed to not finding their product market fit early enough, or at all. Founders overspend time and money trying to find product-market fit and make false starts, follow the wrong signals, and struggle to generate enough revenue to scale and raise funding. And all the while they never really knew who their customers were, what product they really needed, and why they needed it. But it doesnt have to be this way, and founders dont need to face it alone. Through expert guidance and experienced mentorship, every startup can avoid these pitfalls. The ultimate guide for building and scaling any startup sales organization, Sell More Faster shares the proven systems, methods, and lessons from Managing Director of Techstars Austin and sales expert Amos Schwartzfarb. Hear from founders of multi-million-dollar companies and CEOs who learned firsthand with Techstars, the leading mentorship-driven startup accelerator and venture capital firm that has invested in and mentored thousands of companies, collectively representing billions of dollars in funding and market cap. Schwartzfarb, and the Techstars Worldwide Network of more than 10,000 mentors do one thing better than anyone: help startup entrepreneurs succeed. They know how to sell, how to hire people who know how to sell, and how to use sales to gain venture fundingand now you can, too. Sell More Faster delivers the critical strategies and guidance necessary to avoid and manage the hazards all startups face and beat the odds. This valuable resource delivers: A comprehensive playbook to identify product market direction and product market fit Expert advice on building a diverse sales team and how to identify, recruit, and train the kinds of team members you need Models and best practices for sales funnels, pricing, compensation, and scaling A roadmap to create a repeatable and measurable path to find product-market fit. Aggregated knowledge from Techstars leaders and industry experts Sell More Faster is an indispensable guide for entrepreneurs seeking product-market fit, building their sales team, developing a growth strategy, and chasing accelerated, sustained selling success"--
Includes index. - Description based on online resource; title from digital title page (ProQuest Ebook Central, viewed March 3, 2021)
Keywords: Selling; Marketing; Customer relations; New business enterprises; Vente; Nouvelles entreprises; selling; marketing; BUSINESS & ECONOMICS; Sales & Selling; BUSINESS & ECONOMICS; Entrepreneurship